2014
DOI: 10.1016/j.ijhydene.2014.02.120
|View full text |Cite
|
Sign up to set email alerts
|

Material properties and empirical rate equations for hydrogen sorption reactions in 2 LiNH2–1.1 MgH2–0.1 LiBH4–3 wt.% ZrCoH3

Abstract: Abstract2 LiNH 2 -1.1 MgH 2 -0.1 LiBH 4 -3 wt.% ZrCoH 3 is a promising solid state hydrogen storage material with a hydrogen storage capacity of up to 5.3 wt.%. As the material shows sufficiently fast desorption rates at temperatures below 200 °C, it is used for a prototype solid state hydrogen storage tank that is coupled to a HT-PEM fuel cell. In order to perform design simulations for this prototype reactor with a hydrogen capacity of 2kWh el , model equations for the rate of hydrogen sorption reactions are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…2LiNH 2 + 1.1MgH 2 + 0.1LiBH 4 -3 wt. %ZrCoH 3 has been considered as one of the most promising materials for possible real scale applications owing to its excellent hydrogen storage properties [136][137][138]. A prototype tank to feed a 1 kW HT-PEM stack for an Auxiliary Power Unit (APU), was built using this ternary system as storage material.…”
Section: Li-mg-n-h-borohydride Systemsmentioning
confidence: 99%
“…2LiNH 2 + 1.1MgH 2 + 0.1LiBH 4 -3 wt. %ZrCoH 3 has been considered as one of the most promising materials for possible real scale applications owing to its excellent hydrogen storage properties [136][137][138]. A prototype tank to feed a 1 kW HT-PEM stack for an Auxiliary Power Unit (APU), was built using this ternary system as storage material.…”
Section: Li-mg-n-h-borohydride Systemsmentioning
confidence: 99%
“…In the absorption step, the heat of absorption of the MH bed (low temperature) was transferred to the CH bed (higher temperature). The kinetics for the simulation was based on the model by Bürger et al [16]. The viability of the concept was demonstrated by comparing the temperature front in a pure CH bed and in a MH/CH combined bed.…”
Section: Thermolysismentioning
confidence: 99%
“…The combination reactor, initially at room temperature, is filled with hydrogen at 70 bar. Since the AB 5 material, LaNi 4.3 Al 0.4 Mn 0.3 is able to absorb hydrogen very quickly at these ranges of temperature and pressure, its reaction heat ensures the heat up of the complex hydride bed to temperatures above 130 o C. Furthermore, based on the kinetics measurements of the Li-Mg-N-H material at 70 bar, it has been shown that temperatures above 130 o C are required for achieving high hydrogen loading rates [14]. Accordingly, in a combination reactor, the complex hydride charging process is initiated without the need of external heat source integration.…”
Section: Description Of the Studied Configurationmentioning
confidence: 99%
“…Reaction kinetics of both, metal and complex hydrides are determined based on their measured hydrogen charging rates under different conditions of temperature and pressure as described in [14].…”
Section: Kinetics Equationsmentioning
confidence: 99%